O comportamento dos profissionais de saúde frente aos idosos em situação de terminalidade: uma análise de caso - Hospital de Retaguarda Francisco de Assis de Ribeirão Preto - SP - Ali, Angela Maria Amaral Soares Abou (2010)
This work aims to identify the behavior of whealt professionals and the power relationships within old people under biopower optics and at the context of the paliative care. The social and medical advances has provided new ways to maintain and sustain the life, and there are much more situations such that the life is maintaned by machines, increasing the demand for paliative care. New relationships and demands had stabilished, and it was clear that the professionals are unprepared for such situation. The study of Hospital de Retaguarda Francisco de Assis de Ribeirão Preto/SP analyse the activity of the entity and emphatizes the need of implantation the paliative practice in professional formation of that people that will effectivly act in this area